Development of Interactive Learning Media Using Articulate Storyline on Human Respiratory System Material for Grade V at SDN 009 Tarakan - Rhamdan, Donna; Kasih, Nur (Sebatik, 2025)
This research is research and development (Research and Development). This study aims to produce interactive learning media using an articulate storyline in terms of media validation, material, language and also practitioners. In addition, this research was conducted to determine students' interest in interactive learning media using articulate storylines. In this research that has been carried out using the type of research and development, then the research method used is research and development, where in its implementation there is expert validation of the product being developed. Then to answer the research objectives in terms of the attractiveness of the product being developed, the researcher distributed student response questionnaires after the implementation was completed. This research and development procedure uses the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. The validation results obtained from media experts were 80%, material experts 86%, linguists 84%, and practitioner experts 100%. The results of the validation of media experts, materials, discussions and practitioners show that interactive learning media using articulate storylines are very appropriate for use in the learning process. The results of student interest in limited trials were 82% and field trials were 83%. The results of the student interest questionnaire in the limited trials and field trials showed that students were very interested in interactive learning media using articulate storylines.